Targeting Autophagy in the Tumor Microenvironment: New Challenges and Opportunities for Regulating Tumor Immunity - Janji, Bassam; Berchem, Guy; Chouaib, Salem (Frontiers in Immunology, 2018)
Cancer cells evolve in the tumor microenvironment which is now well established as an integral part of the tumor and a determinant player in cancer cell adaptation and resistance to anti-cancer therapies. Despite the remarkable and fairly rapid progress over the past two decades regarding our understanding of the role of the tumor microenvironment in cancer development, its precise contribution to cancer resistance is still fragmented. This is mainly related to the complexity of the "tumor ecosystem" and the diversity of the stromal cell types that constitute the tumor microenvironment. Emerging data indicate that several factors, such as hypoxic stress, activate a plethora of resistance mechanisms, including autophagy, in tumor cells. Hypoxia-induced autophagy in the tumor microenvironment also activates several tumor escape mechanisms which effectively counteract anti-tumor immune responses mediated by natural killer (NK) and cytotoxic T-lymphocytes (CTL). Therefore, strategies aiming at targeting autophagy in cancer cells in combination with other therapeutic strategies have inspired significant interest to overcome immunological tolerance and promote tumor regression. However, a number of obstacles still hamper the application of autophagy inhibitors in clinics. First, the lack of selectivity of the current pharmacological inhibitors of autophagy makes difficult to draw a clear statement about its effective contribution in cancer. Second, autophagy has been also described as an important mechanism in tumor cells involved in presentation of antigens to T cells. Third, there is circumstantial evidence that autophagy activation in some innate immune cells may support the maturation of these cells and is required for their anti-tumor activity. In this review, we will address these aspects and discuss our current knowledge on the benefits and the drawbacks of targeting autophagy in the context of anti-tumor immunity. We believe that it is important to resolve these issues in order to predict the use of autophagy inhibitors in combination with immunotherapies in clinical settings.